2016
DOI: 10.3791/54466
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule Super-resolution Imaging of Phosphatidylinositol 4,5-bisphosphate in the Plasma Membrane with Novel Fluorescent Probes

Abstract: Phosphoinositides in the cell membrane are signaling lipids with multiple cellular functions. Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) is a determinant phosphoinositide of the plasma membrane (PM), and it is required to modulate ion channels, actin dynamics, exocytosis, endocytosis, intracellular signaling, and many other cellular processes. However, the spatial organization of PI(4,5)P 2 in the PM is controversial, and its nanoscale distribution is poorly understood due to the technical limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Secretory cells may utilize such local PI(4,5)P 2 -mediated modulation at vesicle docking and release sites to regulate secretion, without significantly changing other PI(4,5)P 2 -mediated cellular functions. Direct imaging studies showed a heterogeneous PI(4,5)P 2 distribution in intact live cells ( Ji and Lou, 2016 ; Ji et al, 2015 ), although its nanometer-scale patterns are diverse in fixed samples ranging from dense nano-domains ( van den Bogaart et al, 2011 ), microdomains ( Ji et al, 2015 ; Fujita et al, 2009 ), or even distribution ( van Rheenen et al, 2005 ). About 20% of dense core vesicles reside in PI(4,5)P 2 -enriched regions on the fixed cell PM ( Aoyagi et al, 2005 ), and this number increases to 50% when probed with PH PLCδ4 -GFP ( Kabachinski et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretory cells may utilize such local PI(4,5)P 2 -mediated modulation at vesicle docking and release sites to regulate secretion, without significantly changing other PI(4,5)P 2 -mediated cellular functions. Direct imaging studies showed a heterogeneous PI(4,5)P 2 distribution in intact live cells ( Ji and Lou, 2016 ; Ji et al, 2015 ), although its nanometer-scale patterns are diverse in fixed samples ranging from dense nano-domains ( van den Bogaart et al, 2011 ), microdomains ( Ji et al, 2015 ; Fujita et al, 2009 ), or even distribution ( van Rheenen et al, 2005 ). About 20% of dense core vesicles reside in PI(4,5)P 2 -enriched regions on the fixed cell PM ( Aoyagi et al, 2005 ), and this number increases to 50% when probed with PH PLCδ4 -GFP ( Kabachinski et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used a Nikon Ti-E Eclipse inverted-microscope-based imaging system under the control of NIS-Elements AR software as described previously ( Ji et al, 2015 ; Ji and Lou, 2016 ). All experiments were performed at 35°C–37°C; imaging buffers and procedures are described in the Supplemental Information .…”
Section: Methodsmentioning
confidence: 99%
“…Even though PH domain is the best option to visualize PtdIns(4,5)P2, not all of the lipids could be visualized using these methods. For instance, PtdIns(4,5)P2 and PtdIns(3,4,5)P3 might bind with other proteins, thus rendering them incapable of binding with the PH probes or antibodies, which could lead to inaccurate detection (20).…”
Section: Discussionmentioning
confidence: 99%
“…More direct evidence for PI(4)P and PI(4,5)P 2 microdomains is becoming available with development of adequate tools and the use of super resolution microscopy. Such an approach revealed punctate localization of PI(4,5)P 2 at the PM . PIs levels at MCSs are not static and dynamically change during cell stimulation.…”
Section: Introductionmentioning
confidence: 98%